Rancangan Layanan Bimbingan Kelompok Dalam Pengambilan Keputusan Karir Siswa Kelas IX SMP Wahidin Kota Cirebon - Fhany, Siti; Herawati, Endang Sri Budi (Bimbingan dan Konseling, FKIP, Universitas Nahdlatul Ulama Cirebon, 2024)
This study aims to describe the career decision-making ability of grade IX students at SMP Wahidin, Cirebon City. This type of research is descriptive quantitative research with the research population being all grade IX students of SMP Wahidin, Cirebon City with Simple random sampling technique, obtained a research sample of 60 students. The instrument used is a Likert scale that has been tested for instrument validation and reliability. Based on the results of the questionnaire distribution, it is known that the level of career decision-making of grade IX students of SMP Wahidin, Cirebon City is in the low category of 41.70%, career decision-making in the medium category is 33.30%, career decision-making in the high category is 25%. In this case, it shows that BK teachers can provide group guidance services.